Geological interpretation of aeromagnetic data in the middle and lower reaches of the Yangtze river metallogenic belt, China: implications for iron oxide-apatite (IOA) and skarn iron deposit exploration - Ge, Tengfei; Yang, Xue; Fan, Zhenyu; He, Jingzi; Gao, Xiuhe; Li, Xingsu; Qiu, Liang; Fan, Zhengguo; Huang, Xuzhao (Frontiers in Earth Science, 2025)
IntroductionThe Yangtze River Metallogenic Belt (YMB) hosts extensive Mesozoic iron oxide-apatite (IOA) and skarn iron-copper deposits, with significant high-grade iron ore potential. However, the lack of systematic understanding of mineralization types, distribution controls, and metallogenic mechanisms limits exploration efficiency, particularly due to widespread alluvium cover.MethodsWe integrated aeromagnetic data with reduction-to-pole (RTP) transformation, upward continuation, and Curie point isothermal surface calculations. A novel robust principal component analysis (RPCA) based on the inexact augmented Lagrangian method (IALM) was applied to discriminate mineralization zones. Structural controls on deposits were analyzed using updated aeromagnetic and gravity datasets.ResultsProspective zones for iron oxide-apatite (IOA) and skarn mineralization were systematically delineated, demonstrating a robust spatial correlation between ore-bearing magmatic systems and iron deposit localization. The study further highlights the dominance of deep-seated structural frameworks and magmatic conduits in governing the distribution of mineralization, emphasizing their role as primary controls on ore formation.